Development of a Multicomponent Intervention to Prevent Alzheimer's Disease - Saito, Satoshi; Yamamoto, Yumi; Ihara, Masafumi (Frontiers in Neurology, 2019)
Recent advances in vascular risk management have successfully reduced the prevalence of Alzheimer’s Disease (AD) in several epidemiologic investigations. It is now widely accepted that cerebrovascular disease is both directly and indirectly involved in AD pathogenesis. Herein, we review the non-pharmacological and pharmacological therapeutic approaches for AD treatment. MIND (Mediterranean and DASH (Dietary Approaches to Stop Hypertension) Intervention for Neurodegenerative Delay) diet is an important dietary treatment for prevention of AD. Multidomain intervention including diet, exercise, cognitive training, and intensive risk managements also prevented cognitive decline in the Finnish Geriatric Intervention Study to Prevent Cognitive Impairment and Disability (FINGER) study. To confirm these favorable effects of life-style intervention, replica studies are being planned worldwide. Promotion of β-amyloid (Aβ) clearance has emerged as a promising pharmacological approach because insufficient removal of Aβ is more important than excessive Aβ production in the pathogenesis of the majority of AD patients. Most AD brains exhibit accompanying cerebral amyloid angiopathy, and Aβ distribution in cerebral amyloid angiopathy closely corresponds with the intramural periarterial drainage (IPAD) route, emphasizing the importance of Aβ clearance. In view of these facts, promotion of the major vascular-mediated Aβ elimination systems, including capillary transcytosis, the glymphatic system, and IPAD, have emerged as new treatment strategies in AD. In particular, the beneficial effects of cilostazol were shown in several clinical observation studies, and cilostazol facilitated IPAD in a rodent AD model. The COMCID (Cilostazol for prevention of Conversion from MCI to Dementia) trial, evaluating the efficacy of cilostazol for patients with mild cognitive impairment is currently ongoing in Japan. Such therapeutic approaches involving maintenance of cerebrovascular integrity and promotion of vascular-mediated Aβ clearance have the potential to be mainstream treatments for sporadic AD.